One-Pot Multicomponent Domino Synthesis of 4-Aminothiazole-2(3H)-thiones - Hajibabaei, Khadijeh; Zali-Boeini, Hassan (Synlett, 2015)
A new multicomponent domino reaction has been developed for the synthesis of 4-aminothiazole-2(3H)-thiones. Carbon disulfide was successfully used in the preparation of 4-aminothiazole-2(3H)-thione derivatives through reaction with primary amines and 2-bromo-2-arylacetonitriles in the presence of sodium carbonate and a catalytic amount of sodium iodide.
Keywords: amines; catalysis; heterocycles; multicomponent reactions; domino reactions; cyclizations